Interviews as the Basis for Developing a Content Creation App for Generation Z Creators - Nada Larasati Pambudi; Achmad Syarief (Gorga : Jurnal Seni Rupa, 2025)
The rise of digital platforms has enabled Generation Z to become content creators, using social media to express themselves, develop personal brands, and monetize their creativity. Maintaining consistency, navigating algorithm-driven competition, and juggling time constraints with creative output presents unique challenges for this generation. Through in-depth qualitative interviews with ten representative respondents, this study investigates the needs and preferences of Generation Z creators in facing these challenges. The study seeks to understand their creative processes, motivations, problems, and expectations for optimal content creation applications. The results show that the target users prioritize features such as trend analysis, audience research tools, and monetization insights. Performance analysis is one of them. Along with community forums for collaboration and inspiration, they also emphasize the need for organizational tools including moodboards, timelines, and integrated notes. Interestingly, most users prefer mobile-first applications with simple and intuitive designs over desktop-based solutions. They also value paid applications free of ads more than ad-supported free applications. These observations guide this paper to explain the Agile thinking process and design of content creation app development. Prioritizing user-centered design concepts, iterative feedback loops, and adaptability help the proposed app empower Generation Z creators by providing relevant, easy-to-use, and effective tools tailored to their needs.